FAKTOR-FAKTOR FUNDAMENTAL DAN JENIS INDUSTRI TERHADAP CORPORATE SOCIAL RESPONSIBILITY SERTA DAMPAKNYA TERHADAP HARGA SAHAM - Christine Dwi Karya Susilawati; Se Tin; Lidya Agustina (Jurnal Keuangan dan Perbankan, 2014)
Different characteristics could be determined by using three approaches categories: structure, performance, andmarket. Structure was determined by factors associated with the development of the company included firmsize, firm age, and the ability to repay the debt. Performance was determined by quantitative factors includedthe companys liquidity and profitability, while the market was determined by factors namely qualitative formof public shares, and the status of the company. The purpose of this study was to test the influence of fundamentalfactors, namely liquidity, profitability, leverage, stock ownership, firm size, firm age and status of thecompanys CSR, and to test the different types of industries (Consumer Goods, Mining and Forestry sectorsBanking and widespread influence of CSR disclosure in Indonesia). The samples used were 30 companies ofconsumption sector, 31 companies of mining sector and plantation, and 28 companies of banking sector during2010-2012. The companys data was taken from the annual report. Data analysis technique used multipleregression analysis. The results of this study indicated that the stock ownership and firm age had a significanteffect on the area of CSR (CSR Index), and a significant effect on the CSR Index stock price and type industryinfluence on the CSR Index.